Influence of vitamin D on sarcopenia pathophysiology: A longitudinal study in humans and basic research in knockout mice - Takafumi Mizuno; Tohru Hosoyama; Makiko Tomida; Yoko Yamamoto; Yuko Nakamichi; Shigeaki Kato; Minako Kawai‐Takaishi; Shinya Ishizuka; Yukiko Nishita; Chikako Tange; Hiroshi Shimokata; Shiro Imagama; et al. (Wiley, 2022)
Abstract Background Vitamin D is an essential nutrient in musculoskeletal function; however, its relationship to sarcopenia remains ambiguous, and the mechanisms and targets of vitamin D activity have not been elucidated. This study aimed to clarify the role of vitamin D in mature skeletal muscle and its relationship with sarcopenia. Methods This epidemiological study included 1653 community residents who participated in both the fifth and seventh waves of the National Institute for Longevity Sciences, Longitudinal Study of Aging and had complete background data. Participants were classified into two groups: vitamin D‐deficient (serum 25‐hydroxyvitamin D < 20 ng/mL) and non‐deficient (serum 25‐hydroxyvitamin D ≥ 20 ng/mL); they underwent propensity‐score matching for background factors (age, sex, height, weight, comorbidities, smoker, alcohol intake, energy intake, vitamin D intake, steps, activity, season and sarcopenia). Changes in muscle strength and mass over the 4‐year period were compared. For basic analysis, we generated Myf6CreERT2 Vitamin D Receptor (VDR)‐floxed (VdrmcKO) mice with mature muscle fibre‐specific vitamin D receptor knockout, injected tamoxifen into 8‐week‐old mice and analysed various phenotypes at 16 weeks of age. Results Grip strength reduction was significantly greater in the deficient group (−1.55 ± 2.47 kg) than in the non‐deficient group (−1.13 ± 2.47 kg; P = 0.019). Appendicular skeletal muscle mass reduction did not differ significantly between deficient (−0.05 ± 0.79 kg) and non‐deficient (−0.01 ± 0.74 kg) groups (P = 0.423). The incidence of new cases of sarcopenia was significantly higher in the deficient group (15 vs. 5 cases; P = 0.039). Skeletal muscle phenotyping of VdrmcKO mice showed no significant differences in muscle weight, myofibre percentage or myofibre cross‐sectional area; however, both forelimb and four‐limb muscle strength were significantly lower in VdrmcKO mice (males: forelimb, P = 0.048; four‐limb, P = 0.029; females: forelimb, P < 0.001; four‐limb, P < 0.001). Expression profiling revealed a significant decrease in expression of sarcoendoplasmic reticulum Ca2+‐ATPase (SERCA) 1 (P = 0.019) and SERCA2a (P = 0.049) genes in the VdrmcKO mice. In contrast, expression of non‐muscle SERCA2b and myoregulin genes showed no changes. Conclusions Vitamin D deficiency affects muscle strength and may contribute to the onset of sarcopenia. Vitamin D‐VDR signalling has minimal influence on the regulation of muscle mass in mature myofibres but has a significant influence on muscle strength.